A política de formação de professores em cursos da modalidade a distância na UFVJM - Lúcia Ramalho, Mara; Gomes Fernandes , Eduardo; Barbosa dos Reis , Arlete; Arruda , Raquel; Queiroz Santos , Caroline (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
To ensure the quality of education, educational policies have been shown as a key solution brokered by the education and preparation of skilled labor capable of meeting the demands of economic competitiveness as a form of teaching can enable self- learning with the use of teaching resources combined and transmitted by various media /computers, today known as the modality of distance education. To this and, the study used the literature to be an important methodology for conducting the literature review process. Within this context, this work aimed to study the importance of the interaction between theory and practice in teacher education, where it can be concluded that the capacity for reflection and interaction between theory and practice are key elements in the development process training in distance mode in UFVJM.
Keywords: Distance education; Public educational policies